Effects of preoperative nutritional support combined with esketamine on recovery and analgesia after thoracoscopic radical resection of lung cancer in elderly patients - Hou, Yu; Zhan, Zhiru (Frontiers in Surgery, 2026)
AimThis study aims to explore the effects of preoperative nutritional support combined with esketamine on recovery and postoperative pain management in elderly patients undergoing thoracoscopic radical resection for lung cancer.MethodsA total of 165 elderly patients with lung cancer who underwent thoracoscopic radical resection at our hospital between June 2021 and March 2023 were enrolled and divided into a study group (SG, n = 85) and a control group (CG, n = 80). The SG received patient-controlled analgesia with esketamine, sufentanil, dexamethasone, and dexmedetomidine, while the CG received sufentanil, dexamethasone, and dexmedetomidine. The SG received nutritional support both pre- and postoperatively, whereas the CG received it only postoperatively. We compared resting and coughing visual analog scale (VAS) scores; Ramsay sedation scores at 6, 12, 24, and 48 h post-surgery; the number of analgesic pump compressions and drug consumption within 48 h; adverse reactions; recovery indicators; immune function; nutritional status; and quality of life between the groups.ResultsCompared with the CG, the SG demonstrated significantly lower VAS scores at rest and during cough and higher Ramsay sedation scores at 6, 12, 24, and 48 h postoperatively (P < 0.05). The SG also required fewer analgesic pump compressions and lower analgesic drug dosages within 48 h (P < 0.05). The incidence of adverse reactions within 48 h was lower in the SG (P < 0.05). Postoperative recovery indicators, including time to first exhaust, first defecation, and hospitalization, were significantly shorter in the SG (P < 0.05). Furthermore, the SG showed significantly elevated levels of Immunoglobulin G (IgG), IgM, IgA, albumin (Alb), transferrin (TRF), and prealbumin (PAB) (P < 0.05), as well as higher scores across all 36-Item Short Form Health Survey (SF-36) dimensions (P < 0.05).ConclusionPreoperative nutritional support combined with esketamine was associated with reduced pain, improved postoperative recovery indicators, better maintained immune function and nutritional status, and a higher quality of life in elderly patients after thoracoscopic radical resection of lung cancer.